The Relationship Between Perceptions About PAUD Institutions And Parents' Motivation To Enroll Their Children At School - Dirna Maryati Dawa; Kristin Margiani (Universitas Nusa Cendana, 2021)
Parents are responsible for directing their children's education from an early age. Such opinion becomes the reason how parents perceive PAUD institution and influences their motivation to send their children to school. This research, which was conducted for 6 months, aimed to examine whether there is a correlation between perception of PAUD institution and the motivation of parents to send their children to school. The hypothesis proposed in research was there is a correlation between perceptions of PAUD institution with motivation of parents to send their children to school. The data were collected using online questionnaire of Google form, by sending the link to 255 respondents in Kupang City. The data were then analyzed using the Correlational Product Moment (Spearman's rho) formula. The research results showed that there is a significant correlation between perception of PAUD institution and motivation of parents to send their children to school. This is evidenced by the calculated r value of 0.968 with r product moment value of 0.138 (0.968> 0.138), so it can be concluded that when the perception of PAUD institution is positive, the motivation of parents to send their children to school would increase. This finding needs to be reviewed qualitatively to produce more in-depth data.